Ebola Haemorrhagic Fever: An Overview - Kasarla, Rajeshwar Reddy; Verma, Aishwarya; Bhandari, Niru; Pathak, Laxmi (Janaki Medical College Journal of Medical Science, 2024)
Ebola virus disease is a rare but severe, often fatal illness in humans. Fruit bats are the natural reservoirs of Ebola virus, and it is transmitted to humans from wild animals and spreads between humans. Ebola virus is a class A bioterrorism agent, known to cause highly lethal haemorrhagic fever. Clinical symptoms include fever, myalgia, headache followed by vomiting, diarrhea, hemorrhagic rash, bleeding, and multi-organ failure. Vaccines to protect against Ebola have been developed and used to control the spread of Ebola virus disease. Treatment is mainly early supportive care with rehydration and symptomatic treatment. Ebola virus is a neglected pathogen and the knowledge and scientific information on Ebola virus disease is relatively limited and received little attention. Better understanding of ebolavirus disease mechanisms is needed to guide development of drugs, vaccines, and treatment strategies. Hence this comprehensive review on Ebola virus is undertaken to provide an overview of its transmission, pathogenesis, clinical symptoms, differential diagnosis, laboratory diagnosis, treatment, vaccines and preventive aspects and to highlight its importance, and impact on public health and further research.